BANTENESE AUTHORS AND THEIR WORKS - Ade Jaya Suryani (Al Qalam, 2016)
This article describes the authorships in Banten by analyzing the authors as follow: Syaikh Yusuf al-Maqassari; Syekh Nawawi AI-Bantani; Hoesein Djajadiningrat and his brothers; Gola Gong and other new generation authors. It also tries to explain the biography of the authors, their works, and social conditions that have probably influenced their authorships. Key words: Authorship, Banten, Syaikh Yusuf al-Maqassari, Syekh Nawawi AI-Bantani, Hoesein Djajadiningrat and Gola Gong